Radial distribution of lead and lead isotopes in stem wood of Norway spruce: a reliable archive of pollution trends in Central Europe - Novák, Martin; Mikova, Jitka; Krachler, Michael; Kosler, Jan; Erbanova, Lucie; Prechova, Eva; Jackova, Iva; Fottova, Daniela (Geochimica et cosmochimica acta, 2010)
Annual growth rings of a common hardwood species, Picea abies L., were investigated as a potential archive of past atmospheric Pb pollution. Wide distribution of trees in terrestrial settings and straightforward chronology are two advantages of this potential geochemical archive, but several processes described in the literature may obscure the trends in past Pb deposition. These confounding factors include, e.g., radial post-depositional mobility of Pb in xylem, and ecosystem acidification leading to higher bioavailability of Pb. One- to five-year annual wood increments were analyzed for Pb concentrations and 206Pb/207Pb ratios at Jezeri (JEZ), Uhlirska (UHL) and Na Lizu (LIZ), three sites in the Czech Republic, differing in atmospheric Pb loads. Three to four trees per site were included in the study. Distinct Pb concentration maxima between 1960 and 1990 at the two heavily polluted sites (JEZ and UHL) coincided with historical Pb emissions known from inventories of industrial production. No Pb concentration maxima were found at one site, LIZ, situated in a national park 150km from major pollution sources. Spruce tree rings from JEZ, located just 5km from coal-burning power stations, contained a large proportion of coal-derived Pb (a high-206Pb/207Pb ratio of 1.19). A coal-related maximum in 206Pb/207Pb in JEZ tree rings was found using two different analytical techniques, laser-ablation multi-collector ICP MS, and single-collector sector-field ICP MS. In a three-isotope graph (206Pb/207Pb vs. 208Pb/207Pb), tree-ring data plotted into the field of ombrotrophic (i.e., rain-fed) peat bogs, suggesting negligible contribution of bedrock-derived Pb in the xylem. We concluded that none of the potential confounding factors played a major role at our sites. Annual growth rings of P. abies in Central Europe faithfully recorded historical changes in atmospheric Pb depositions.
Gesehen am 22.05.2023